1992
DOI: 10.1007/bf02251969
|View full text |Cite
|
Sign up to set email alerts
|

Normal variation in anorectal manometry

Abstract: A study was performed to define the normal range of values for anorectal manometry. Normal volunteers were divided according to gender and parity. There were 20 males, 21 nulliparous females, and 18 multiparous females among the 59 subjects. Anorectal manometry using a radial eight-port catheter was performed during resting and squeezing maneuvers of the anal sphincter. Computerized data analysis and three-dimensional imaging were used to calculate sphincter length at rest and squeeze, mean maximum resting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 11 publications
4
36
0
1
Order By: Relevance
“…We observed an age-and parityrelated diminished squeezing pressure. However, in agreement with several other studies, this decline was not significant [13,14] .…”
Section: Discussionsupporting
confidence: 75%
“…We observed an age-and parityrelated diminished squeezing pressure. However, in agreement with several other studies, this decline was not significant [13,14] .…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, measurement of functional canal length was not possible with the manometric equipment used in this study, however, no relationship between EAS shortening and incontinence scores has been found. Previous work investigating differences in physiologic measurements of the anal canal has however not shown a shortening of the functional anal canal length with parity 13 , although no study has measured functional canal length before and after delivery in the same women. Furthermore, sphincter shortening after childbirth has important implications if surgery to the anal canal is being considered, because similar surgery involving the anterior canal will involve a greater proportion of the EAS in parous than nulliparous women.…”
Section: Discussionmentioning
confidence: 90%
“…However, published normal values differ. This can be related, at least in part, to differences in methodology, in the small numbers of healthy people investigated, and to the comparison of (only) 2 groups with an large age difference [6,7]. Yet, it might also be due to discrepancies in the study population (female:male ratio, age distribution) since Felt-Bersma et al [8] observed a broad range of anal pressures when measuring normal individuals of different ages and gender.…”
Section: Introductionmentioning
confidence: 99%